2014
DOI: 10.1002/pc.23035
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nylon 6,6 nanofibrous mats on thermal properties and delamination behavior of high performance CFRP laminates

Abstract: Nylon 6,6 electrospun nanofibrous membranes interleaved in "high performance" Carbon Fiber Reinforced Polymer (CFRP) laminates have been proposed as a means to provide a high threshold value to delamination on structural sites where composites are more prone to develop such failure. A model, highly crosslinked, thus inherently brittle, epoxy matrix was selected for its high Young's modulus and glass transition temperature exceeding 250 C. The influence of the Nylon 6,6 nanofibers on the curing behavior of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 24 publications
(36 reference statements)
0
28
0
Order By: Relevance
“…The main issues with the use of CNT and CNF are linked to health dangerousness [85] and difficulties in mixing and homogenizing with the matrix [86]. Authors considered out of the scope of this literature, and therefore did not treat, studies on nanofibers embedded in pure matrix [60,[87][88][89][90][91][92][93][94], on the single nanofiber [95][96][97][98], and on numerical simulations of nanomodified composites [65,[99][100][101][102].…”
Section: Electrospinningmentioning
confidence: 99%
See 3 more Smart Citations
“…The main issues with the use of CNT and CNF are linked to health dangerousness [85] and difficulties in mixing and homogenizing with the matrix [86]. Authors considered out of the scope of this literature, and therefore did not treat, studies on nanofibers embedded in pure matrix [60,[87][88][89][90][91][92][93][94], on the single nanofiber [95][96][97][98], and on numerical simulations of nanomodified composites [65,[99][100][101][102].…”
Section: Electrospinningmentioning
confidence: 99%
“…• resin reinforcement [23,60,[87][88][89][90][91][92][93][94], detected by several authors, using a different type of polymers. In [94] it is demonstrated that using an hybrid electrospinning-electrospraying method (electrospraying uses polymers with much shorter chains which end deposited as particles rather than fibers), a resin containing 0.13% weight content of fiber was 700% stronger, 250% stiffer, and more ductile than the non-modified one.…”
Section: Mode Imentioning
confidence: 99%
See 2 more Smart Citations
“…As some of the authors have already demonstrated, interleaving small diameter fibres between one or more interfaces improves strength, toughness and delamination resistance of composites without reducing the in-plane properties or adding weight [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%